Kelainan Kongenital Tidak Terbentuknya Arteri Koroner Kiri Utama, dan Sumber Left Anterior Descending Coronary Artery Berasal dari Sinus Aorta Kanan. - fatimah shahab (Faculty of Medicine Universitas Mataram, 2022)
Congenital coronary artery anomalies are rare. Clinically, coronary artery anomalies can be benign or life-threatening depending on the prognosis. This case report aims to describe a patient who presented with atypical chest pain as an early symptom who underwent CT scan. The CT scan image showed total calcium score 0, anomalous origin of the LAD from the right aortic sinus, and no evidence of plaque or stenosis at LM, LAD, LCX, RCA. This anomaly is included in the classification of anomalous origin. LAD originates from the right aortic sinus, with a pre-pulmonic pathway so that the hemodynamics is still good and is classified as an anomaly without ischemia. Keywords: Coronary artery anomaly, Absence of LMCA, Anomalous origin.